Satellite cell activity is differentially affected by contraction mode in human muscle following a work-matched bout of exercise - Hyldahl, Robert D.; Olson, Ty; Welling, Tyson; Groscost, Logan; Parcell, Allen C. (Frontiers in Physiology, 2014)
Optimal repair and adaptation of skeletal muscle is facilitated by resident stem cells (satellite cells). To understand how different exercise modes influence satellite cell dynamics, we measured satellite cell activity in conjunction with markers of muscle damage and inflammation in human skeletal muscle following a single work- and intensity-matched bout of eccentric (ECC) or concentric contractions (CON). Participants completed a single bout of ECC (n=7) or CON (n=7) of the knee extensors. A muscle biopsy was obtained before and 24 h after exercise. Functional measures and immunohistochemical analyses were used to determine the extent of muscle damage and indices of satellite cell activity. Cytokine concentrations were measured using a multiplexed magnetic bead assay. Isokinetic peak torque decreased following ECC (p<0.05) but not CON. Greater histological staining of the damage marker Xin was observed in muscle samples of ECC vs CON. Tenasin C immunoreactivity increased 15 fold (P<0.01) following ECC and was unchanged following CON. The inflammatory cytokines interferon gamma-induced protein 10 (IP-10) and monocyte chemotactic protein 1 (MCP-1) increased pre- to post-ECC (4.26 ± 1.4 vs. 10.49 ± 5.8 pg/ml, and 3.06 ± 0.7 vs. 6.25 ± 4.6 pg/ml, respectively; p<0.05). There was no change in any cytokine post-CON. Satellite cell content increased 27% pre- to post-ECC (0.10 ± 0.031 vs. 0.127 ± 0.041, respectively; p<0.05). There was no change in satellite cell number in CON (0.099 ± 0.027 vs. 0.102 ± 0.029, respectively). There was no fiber type-specific satellite cell response following either exercise mode. ECC but not CON resulted in an increase in MyoD positive nuclei per myofiber pre- to post-exercise (p<0.05), but there was no change in MyoD DNA binding activity in either condition. In conclusion, ECC but not CON results in functional and histological evidence of muscle damage that is accompanied by increased satellite cell activity 24 h post-exercise.